Characterisation and multifaceted anisotropy assessment of Corvio sandstone for geological CO2 storage studies. (27th October 2016) - Falcon‐Suarez, Ismael; Canal‐Vila, Jacobo; Delgado‐Martin, Jordi; North, Laurence; Best, Angus
ABSTRACT: We present a comprehensive characterisation of the physical, mineralogical, geomechanical, geophysical, and hydrodynamic properties of Corvio sandstone. This information, together with a detailed assessment of anisotropy, is needed to establish Corvio sandstone as a useful laboratory rock‐testing standard for well‐constrained studies of thermo–hydro–mechanical–chemical coupled phenomena associated with CO2 storage practices and for geological reservoir studies in general. More than 200 core plugs of Corvio sandstone (38.1 and 50 mm diameters, 2:1 length‐to‐diameter ratio) were used in this characterisation study, with a rock porosity of 21.7 ± 1.2%, dry density 2036 ± 32 kg m −3, and unconfined compressive and tensile strengths of 41 ± 3.28 and 2.3 ± 0.14 MPa, respectively. Geomechanical tests show that the rock behaves elastically between ∼10 and ∼18 MPa under unconfined conditions with associated Young's modulus and Poisson's ratio of 11.8 ± 2.8 GPa and 0.34 ± 0.01 GPa, respectively. Permeability abruptly decreases with confining pressure up to ∼10 MPa and then stabilises at ∼1 mD. Ultrasonic P‐ and S‐wave velocities vary from about 2.8–3.8 km s −1 and 1.5–2.4 km s −1, respectively, over confining and differential pressures between 0.1 and 35 MPa, allowing derivation of associated dynamic elastic moduli. Anisotropy was investigated using oriented core plugs for electrical resistivity, elastic wave velocity and attenuation, permeability, and tracer injection tests. Corvio sandstone shows weak transverse isotropy (symmetry axis normal to bedding) of <10% for velocity and <20% for attenuation.